Private Infrastructure - World Bank (World Bank, Washington, DC, 2012)
Drawing on the World Bank's Private Participation in Infrastructure Project Database, this Note provides an overview of private activity in infrastructure in developing countries between 1990 and 2000. Three main trends characterized that decade: Private activity in infrastructure grew each year except 1998 and 1999. Most developing countries introduced some form of private activity in infrastructure. But Latin America and East Asia captured most of the investment. The 1990s marked the reemergence of private participation in infrastructure in the developing world after decades of nationalization and public sector management. Between 1990 and 2000, 130 developing countries had infrastructure projects with private participation, and 54 of them introduced private participation in at least three infrastructure sectors. During that decade developing country governments transferred to the private sector the operating or construction risk, or both, for more than 2,300 infrastructure projects and attracted investment commitments of almost US$690 billion.1 Those projects were implemented under a range of schemes: management contracts, divestitures, and greenfield facilities (build-operate-own contracts, build-operate-transfer contracts, and merchant facilities).